Planejamento e controle físico/financeiro em obras de edificação – Estudo de caso na Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Brazil is in a crisis, as a resulto f the construction industry shows weak and afraid in relation to new developments. This table brings out the importance of proper management of Works, because only from a correct management construction could succeed. In a view of this, it is necessary that appropriate techniques for planning and control Works are well implemented and managed. In this context, this paper aims to study the main tools for planning and control Works, its importance, its applications and limitations; and then shows the realization of a case study in multicampi work of the Student House João de Barro, Federal University of Pampa (UNIPAMPA). In this study, using the methodologies most expoited by literature review, there was the idealization of the planning of the whole building, which is in the design stage in some campus, and others are running. Analysis of projects and the Project budget were made, from which defined the work break structure (WBS), which in turn has made it possible to estimate durations of services and assign relationships between them. As results were obtained timelines, diagrams and charts with curves and histograms, representing all the processes to be performed during construction. Effective controlo f schedule could not be done, however it proposed a physical / financial control plan for the work. This plan, in addition to monitoring, is based on specific performance indicators, suggestions and recommendations that can be followed over the Project implementation period. At the end of the proceedings could be seen the importance of proper planning and control of activities with the implementation of the techniques studied, which presente themselves as a powerful management tool in construction.
Keywords: Civil engineering; Planning; Control; Construction; Management; Engenharia civil; Planejamento; Controle; Construção civil; Gerenciamento; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL